Academic burnout among undergraduate nursing students: Predicting the role of sleep quality and healthy lifestyle - Habibolah Naderi; Hamidreza Dehghan; Shahrbanoo Dehrouyeh; Elaheh Tajik (Tabriz University of Medical Sciences, 2021)
Background: Academic burnout is a serious threat that can affect any student's academic life, especially nursing students. Sleep quality and a healthy lifestyle are variables are related to academic burnout. This study aimed to predict undergraduate nursing students' academic burnout based on sleep quality and lifestyle. Methods: The study was descriptive and correlational in design. The statistical population included all undergraduate nursing students of the Razi School of Nursing and Midwifery at the Kerman University of Medical Sciences (Kerman, Iran; 2016-2017 academic year). Of 270 students,143 students were selected using a random cluster sampling method. The Academic Burnout Questionnaire, the Pittsburgh Sleep Quality Index (PSQI), and the LifeStyle Inventory were used to collect data. A linear regression analysis using the enter method was employed for data analysis. Results: There was a significantly positive correlation between students' academic burnout and total PSQI score (P=0.000, r=0.547) and some of its sub-scales, including subjective sleep quality (P=0.000, r=0.607), sleep latency (P=0.019, r=0.196), sleep duration (P=0.014, r=0.206), sleep disturbance (P=0.000, r=0.346), and daytime dysfunction due to sleepiness (P=0.000, r=0.654). Conversely, the relationship between students' academic burnout and healthy lifestyle was negatively significant (P=0.000, r=-0.507). Thus, the potential for undergraduate nursing students' academic burnout can be predicted by sleep quality and lifestyle (P=0.000, F=23.480). Conclusions: By improving sleep quality and living a healthier lifestyle, students may be less likely to experience academic burnout.